Treatment protocol for unilateral cleft lip and palate patients: questioned by two case reports - Aly Medhat; Verdonck Anna; Carels Carine; Willems Guy (Sciendo, 2005)
Background: The types and severity of clefts as well as palatal development and growth in children with repaired cleft lip and palate deformities can vary greatly. Independent of the technique used surgery produces scar tissue, which restricts palatal growth so that by the second decade many patients have an underdeveloped maxilla. Experience has shown that the maxillary retrognathism found in many cleft patients is not amenable to nonsurgical correction. Few long-term studies have evaluated the procedures, sequencing and timing of the treatment methods found to give the best results. This lack of reliable information means there is a serious gap in our ability to assess the value of different treatment modalities.